Features and mechanisms of propofol-induced protein kinase C (PKC) translocation and activation in living cells - Noguchi, Soma; Kajimoto, Taketoshi; Kumamoto, Takuya; Shingai, Masashi; Narasaki, Soshi; Urabe, Tomoaki; Imamura, Serika; Harada, Kana; Hide, Izumi; Tanaka, Sigeru; Yanase, Yuhki; Nakamura, Shun-Ichi; et al. (Frontiers in Pharmacology, 2023)
Background and Purpose: In this study, we aimed to elucidate the action mechanisms of propofol, particularly those underlying propofol-induced protein kinase C (PKC) translocation. Experimental Approach: Various PKCs fused with green fluorescent protein (PKC-GFP) or other GFP-fused proteins were expressed in HeLa cells, and their propofol-induced dynamics were observed using confocal laser scanning microscopy. Propofol-induced PKC activation in cells was estimated using the C kinase activity receptor (CKAR), an indicator of intracellular PKC activation. We also examined PKC translocation using isomers and derivatives of propofol to identify the crucial structural motifs involved in this process. Key Results: Propofol persistently translocated PKC from conventional PKCs and PKC from novel PKCs (nPKCs) to the plasma membrane (PM). Propofol translocated PKC and PKC of nPKCs to the Golgi apparatus and endoplasmic reticulum, respectively. Propofol also induced the nuclear translocation of PKC of atypical PKCs or proteins other than PKCs, such that the protein concentration inside and outside the nucleus became uniform. CKAR analysis revealed that propofol activated PKC in the PM and Golgi apparatus. Moreover, tests using isomers and derivatives of propofol predicted that the structural motifs important for the induction of PKC and nuclear translocation are different. Conclusion and Implications: Propofol induced the subtype-specific intracellular translocation of PKCs and activated PKCs. Additionally, propofol induced the nuclear translocation of PKCs and other proteins, probably by altering the permeability of the nuclear envelope. Interestingly, propofol-induced PKC and nuclear translocation may occur via different mechanisms. Our findings provide insights into the action mechanisms of propofol.